Mechanical and Thermal Properties of Nano-Sio2 Epoxy Coir Fiber Reinforced Composites with Conventional Epoxy-Based Composites - Vishav Gupta; Dr. Sandeep Gandotra; Dr. Naveen Beri (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
Comprehensive analysis of nano-SiO2-reinforced epoxy composites and compared them with commonly used coir fabric. For both static and dynamic applications, coir fabric composites were considered as suitable material due to their strength and biodegradability. In this research, 15 nm SiO2 nano powder was used as a filler. Several composite laminates with different filler concentrations of 2%, 3%, and 5% SiO2 by weight of the epoxy resin were fabricated using hand lay-up method (LY556). Various testing methods, including tensile testing, impact testing, wear testing, moisture absorption testing, and thermogravimetric analysis (TGA), were employed to evaluate the properties of the final composite. The results indicated that the mechanical and thermal characteristics of the produced composite were significantly influenced by the filler material.